Dietary Habits and Portion Sizes Associated with Overweight and Obesity Among Undergraduate Students in Ogun State, Nigeria (P04-184-19) - Oladoyinbo, Catherine (Curr Dev Nutr, 2019)
OBJECTIVES: The study aims to assess the type, frequency and portion sizes of foods and drinks commonly consumed that are associated with overweight and obesity among undergraduate students in Ogun state, Nigeria. METHODS: The cross-sectional study was conducted among 1050 undergraduate students from twelve (12) tertiary institutions in Ogun State. A structured questionnaire was used to assess their personal characteristics. Weight, height, waist and hip circumference were measured using appropriate instruments and techniques. Body Mass Index (BMI) was calculated and categorized according to the WHO standard. An adapted dietary habit and semi-quantitative food frequency questionnaire was used to assess dietary habits, type, frequency and portion sizes of foods and beverages consumed. The WHO Global Physical Activity Questionnaire was used to assess physical activity level. Descriptive (mean, Standard deviation, median, frequencies) and inferential (Chi-square, correlations) were done. RESULTS: The mean age of the students was 21.76 ± 2.15 and the prevalence of underweight, normal weight, overweight and obesity were 13.8%, 67.5%, 15.1% and 3.5% respectively. Majority (97.1%) of the students consume snack with 38.9% of them snacking on pastries daily. Also, 90.1% skip at least one meal daily with 41.4% skipping breakfast and 29.7% consumes fast foods. The most frequently consumed food was white rice, pasta and bread with a median portion of 450 g, 470 g and 220 g per capita. Carbonated soft drinks are the most frequently consumed beverages with a median consumption of 350 ml. Fruits and vegetable consumption was poor as 17% and 13.1% consume them daily. A significant relationship was found between the BMI and snacking pattern (χ2 = 16.07; P = .0.001), overweight and obesity was significantly higher among the female respondents (χ2 = 29.99; P < 0.001). Also, a positive significant correlation was found between BMI and quantity soft drink consumed (r = 0.96; P = 0.002). No significant association was found between BMI and physical activity (χ2 = 9.88; P = 0.115). CONCLUSIONS: Both underweight and overweight is prevalent among the respondents, snacking and meal skipping is also practiced by majority of the students and large portions of soft drinks consumed has a strong correlation with body mass index. FUNDING SOURCES: None. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: